KERANGKA PARADIGMATIK TAFSIR ALQUR’AN ALKARIM KARYA MAHMUD YUNUS - Zulyadain Zulyadain (Al-A'raf: Jurnal Pemikiran Islam dan Filsafat)
This study aims to discuss the Quranic interpretation in Indonesia early period, with Tafsir of Alqur’an Alkarim written by Mahmud Yunus as its object of study. Through the epistemological analysis or interpretation structure method which is focused on the two important aspects; methodology and structure of interpretation, the results revealed that tafsir in the early period of Islam in Indonesia as part of the renewal effort (tajdid) in order that people would be able to understand the message and meaning of Alqur’an comprehensively. Tafsir Alquran Alkarim written by Mahmud Yunus, which is born shortly before the Youth Pledge in 1928 and written in the Indonesian language is an effort in order that the meaning and message of Alqur’an being able to be understood by all levels of Indonesian society. The presentation model used is an explanatory model with sub-explanation. There are four patterns of its structural analysis of interpretation: i.e. ijmali, simple thematic, quotation and nahwu. The instrumental interpretation used is tafsiriyah tarjamah with the translation pattern of harfiyyah and maknawiyyah.